PENCEGAHAN RADIKALISME KEAGAMAAN DI PEMUDA INDONESIA : STUDI KASUS ORGANISASI MAHASISWA ISLAM (HMI, PMII, IMM, KAMMI) PERIODE PENGURUS 2017-2021 - Fatahillah, Arjun; Luthfi Zuhdi, Muhammad; Mukhtar, Sidratahta (Journal of Terrorism Studies, 2022)
The current definition of radicalism is unclear. Distrust of the government and fanaticism in religious groups fueled radicalism. The state of Indonesia is one of the countries with the majority of people having Islam in the world. The role of students as part of youth in Indonesia is very important for the future of the nation. The purpose of this study was to analyze the prevention of religious radicalism in the Islamic Student Organization. Qualitative research methods with observation, interviews, and secondary data. The triangulation method was used to validate the research findings. Islamic Student Organization Case Studies: HMI, PMII, IMM, and KAMMI. The Islamic Student Organization has unique and distinct religious characteristics. The leadership of Islamic mass organizations has a different cadre system and is able to prevent religious radicalism. Government support is needed to suppress radicalism by examining several policies, including policies that create a dichotomy between Religion and State.